Criticism of the requirements of "New Education" to school - Mikėnas , V. (Psichologija, 1971)
The article deals with the character of critical remarks of teachers and educators of bourgeois Lithuania concerning the requirements of "new education" to school. The view of J. Vabalas-Gudaitis, founder of the experimental psychology and pedagogics in Lithuania, are analysed more thoroughly. The ideas of "new education" found many supporters in Lithuania since their rise in Western Europe and the USA. The theory (pedocentrism, etc.) and the practical experience of "new schools" (boarding schools, conditions of education, selfgovernment, etc.) were assessed critically and that created the necessary prerequisites for new and independent progressive ideas in Lithuanian pedagogics.